Sustainable Transport: The Role of Clean Energy, Mass Rapid Transit, Non-motorized Mobility, and Challenges to Achievement - Muji Setiyo (Automotive Experiences, 2023)
Sustainable transport is an important concept to reduce dependence on fossil fuels and to realize a cleaner and more sustainable future. This is achieved through the use of clean energy, low-emission vehicles, efficient use of resources, and transportation planning that considers the needs of the environment and society. Therefore, the use of clean and renewable energy sources, Mass Rapid Transit (MRT), and non-motorized mobility continue to be promoted to support a sustainable transportation system. However, there are several challenges that must be overcome to achieve a truly sustainable transport system, including the costs of switching to clean energy and low-emission vehicles, the lack of infrastructure to support sustainable transport, and the need for greater public awareness and education. about the benefits of sustainable transportation.